Generation of Germ-Free Ciona intestinalis for Studies of Gut-Microbe Interactions - Leigh, Brittany A.; Liberti, Assunta; Dishaw, Larry J. (Frontiers in Microbiology, 2016)
Microbes associate with animal hosts, often providing shelter in a nutrient-rich environment. The gut, however, can be a harsh environment with members of the microbiome settling in distinct niches resulting in more stable, adherent biofilms. These diverse communities can provide orders of magnitude more gene products than the host genome; selection and maintenance of a functionally relevant and useful microbiome is now recognized to be an essential component of homeostasis. Germ-free (GF) model systems allow dissection of host-microbe interactions in a simple and direct way where each member of the symbiosis can be studied in isolation. In addition, because immune defenses in the gut are often naive in GF animals, host immune recognition and responses during the process of colonization can be studied. Ciona intestinalis, a basal chordate, is a well-characterized developmental model system and holds promise for addressing some of these important questions. With transparent juveniles, Ciona can be exposed to distinct bacterial isolates by inoculating GF artificial seawater; concentrated bacteria can subsequently be visualized in vivo if stained fluorescently. Rearing GF Ciona is a first step in untangling the complex dialogue between bacteria and innate immunity during colonization.